Stability of a Second Order of Accuracy Difference Scheme for Hyperbolic Equation in a Hilbert Space - Allaberen Ashyralyev; Mehmet Emir Koksal (Discrete Dynamics in Nature and Society)
The initial-value problem for hyperbolic equation d2u(t)/dt2+A(t)u(t)=f(t)(0≤t≤T), u(0)=ϕ,u′(0)=ψ in a Hilbert space H with the self-adjoint positive definite operators A(t) is considered. The second order of accuracy difference scheme for the approximately solving this initial-value problem is presented. The stability estimates for the solution of this difference scheme are established.